PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA DAN DAMPAKNYA TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Movie Rahmatika Suryani (Universitas Jember, 2018)
The main objective is to establish board independent, audit committees, institutional ownership, and management ownership as part of a good corporate governance on earnings managemement and earnings management on return on assets and return on equity at manufacturing companies which listed in Indonesia Stock Exchange (IDX) from 2011 to 2013. The method of selecting sample research using census sampling method. Acquired 206 manufacturing companies. Data analysis used multiple regression analysis and simple regression analysis using SPSS version 18. The results show that board independent and audit committees are not proven to earnings management while institutional ownership and management ownership have significant positive effect to earnings management. Furthermore earnings management practices undertaken by the company proved to improve the financial performance of the company. Keywords: good corporate governance, earning management, financialperformance